The type of the enigmatic creeping water bug Naucoris sumatranus FIEBER, 1851 (Hemiptera: Heteroptera: Naucoridae) - Zettel, Herbert (Zootaxa, 2011)
In the Malesian faunal region the Naucoridae or creeping water bugs comprise 79 described species, which have been mostly subject to recent reviews and revisions (see checklist and references in Chen et al. 2005; and Zettel 2007, Polhemus & Polhemus 2008, Polhemus et al. 2008, Sites & Suputa 2008, Sites & Vitheepradit 2011). However, an exception, Naucoris sumatranus remained untreated for 160 years, since its short original description by Fieber in 1851. To fill this gap the type specimen in the Natural History Museum Vienna is redescribed and the species identity is discussed.